Enhanced Hydro-Actuation and Capacitance of Electrochemically Inner-Bundle-Activated Carbon Nanotube Yarns - Son, Wonkyeong; Lee, Jae Myeong; Chun, Sungwoo; Yu, Seongjun; Noh, Jun Ho; Kim, Hyeon Woo; Cho, Sung Beom; Kim, Seon Jeong; Choi, Changsoon (ACS Applied Materials and Interfaces, 2023)
Recently, several attempts have been made to activate or functionalize macroscopic carbon nanotube (CNT) yarns to enhance their innate abilities. However, a more homogeneous and holistic activation approach that reflects the individual nanotubes constituting the yarns is crucial. Herein, a facile strategy is reported to maximize the intrinsic properties of CNTs assembled in yarns through an electrochemical inner-bundle activation (EIBA) process. The as-prepared neat CNT yarns are two-end tethered and subjected to an electrochemical voltage (vs Ag/AgCl) in aqueous electrolyte systems. Massive electrolyte infiltration during the EIBA causes swelling of the CNT interlayers owing to the tethering and subsequent yarn shrinkage after drying, suggesting activation of the entire yarn. The EIBA-treated CNT yarns functionalized with oxygen-containing groups exhibit enhanced wettability without significant loss of their physical properties. The EIBA effect of the CNTs is experimentally demonstrated by hydration-driven torsional actuation (∼986 revolutions/m) and a drastic capacitance improvement (approximately 25-fold).
Keywords: Activated carbon nanotubes; Activation approaches; Activation process; Carbon nanotube yarns; Electrochemical activation; Electrochemical voltage; Electrochemicals; Hydro-actuation; Inner bundle; Intrinsic property; capacitances; carbon nanotube yarns; electrochemical activation; hydro-actuations; inner bundles